HUBUNGAN ANTARA AKTIVITAS SEDENTARY LIFESTYLE DAN ASUPAN GIZI TERHADAP KEJADIAN OVERWEIGHT PADA ORANG DEWASA DI DISPORAPAR KABUPATEN JOMBANG - Husain , Rindang Muhammad; Yuliastrid , Dita; Noordia , Anna; Bakti, Ananda Perwira (Jurnal Porkes, 2024)
Low physical activity and the tendency to stay still without doing physical activities often cause the incidence of overweight in a person to increase. The purpose of this study was to examine the relationship between sedentary lifestyle activities and nutritional intake on the incidence of overweight in adults at Disporapar Jombang Regency with a total sample of 25 male and female employees aged 40-55 years. This type of research is a non-experimental study with a quantitative descriptive approach using a correlational design. The results of data analysis show that the average Disporapar employee has a moderate level of sedentary lifestyle activity (56%) then has a normal nutritional intake (56%) and has an overweight nutritional status (56%). The results of the research analysis show that there is a significant relationship between sedentary lifestyle activities and nutritional intake with the incidence of overweight in adults, namely with a sig value of 0.003 <0.05 and there is a contribution between sedentary lifestyle activities and nutritional intake with the incidence of overweight in adults by 41.3%. It can be concluded that there is a significant relationship between sedentary lifestyle activities and nutritional intake on the incidence of overweight in adults at Disporapar Jombang Regency.